Beautifying our Kansas country homes - Eastman, Robert Edward (My University, 1900)
Introduction: A discourse on this subject may to some seem out of place and altogether base in its implications; and, it is with complaisance and a feeling of deference that the writer labors under in the attempt to dabble in the philosophy of this problem. Yet a cursory glance over the field makes it apparent that there is ample ground for suggestion and criticism, and that more attention, more practical work and application in beautifying our country homes would result in an incalculable increase in benefits, both socially and financially. To-day, if one would stand and gaze with a critical eye, or travel and observe the dwelling places of our citizens, he would be forced to acknowledge that he sees not homes – scarcely the semblance of homes, - but in reality he sees a house, perhaps with a few dilapidated accompaniments. The reason why our country homes should receive the attention of this article is this: In the country districts lie the redeeming qualities and the future welfare of our state. In our once broad and uninhabited prairies is now the source of the life giving energy of progress. On this undulating plain of fertility and wealth are found the homes of our farmers, the active element and mainstay of our development, the bone and sinew, and the hope of further advancement. Under these conditions, why should we find so many dwelling places lacking the fundamental qualities of a home, places that are surrounded by unsightly objects, having their yards strewn with the wrecks of bygone machinery, the debris of the prehistoric woodpile, and all imaginable refuse of a quarter or a half a Century of man’s inhabitancy that all in all gives one but a feeling of weariness and disgust.
Citation: Eastman, Robert Edward. Beautifying our Kansas country homes. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Kansas; Landscaping; Gardening; Theses